"MCR-Click" synthesis of coumarin-tagged macrocycles with large Stokes shift values and cytotoxicity against human breast cancer cell line MCF-7. Issue 22 (31st May 2017) - Raj, P. Jithin; Bahulayan, D.
Graphical abstract: Highlights: An easy three step process for the peptidomimetic macrocycles with controlled ring size. All molecules showed significantly high Stokes shift useful for the development of probes with high signal to noise ratio. All molecules are multipurpose in nature having high cytotoxicity toward human breast cancer cell line MCF-7. Abstract: A three step "MCR-Click" strategy has been developed for the synthesis of a library of coumarin-tagged macrocycles with varying ring size from 11 to 18. The coumarin moiety connected to the peptidomimetic macrocycles thorough a keto-methylenic spacer helps the molecules to become optical systems with controlled emission properties. All the twelve macrocycles developed are emitting in the green region with high Stokes shift values indicating the potential of these molecules as probes for bioimaging applications. Similarly, the excellent cytotoxicity exhibited by the molecules toward human breast cancer cell line (MCF-7) further indicating the possibilities of these new macrocycles as potential anticancer/antitumor agents.